The impact of interleukin serum levels on the prognosis of patients undergoing venoarterial extracorporeal membrane oxygenation. Issue 8 (8th March 2020) - Schopka, Simon; Philipp, Alois; Müller, Thomas; Lubnow, Matthias; Lunz, Dirk; Unterbuchner, Christoph; Rupprecht, Leopold; Keyser, Andreas; Schmid, Christof
Abstract: Extracorporeal life support is increasingly used in the treatment of patients presenting with cardiogenic shock or in need of cardiopulmonary resuscitation. Identifying therapeutic targets and factors associated with the prognosis are highly desirable. The present study analyzed the impact of interleukin 6 and 8 on the outcome of patients undergoing venoarterial extracorporeal membrane oxygenation (VA ECMO). Interleukin 6 and 8 serum levels of 329 patients were analyzed prior to, on days 1 and 5 of VA ECMO therapy. Interleukin 6 and 8 serum levels of surviving and nonsurviving patients were compared. At time points with significant differences, receiver operating characteristics and cutoff levels were analyzed to determine the prognostic value of interleukin serum levels. Survival analysis was performed to compare patients above and below cutoff levels. Interleukin 6 serum levels were significantly elevated in nonsurviving patients prior to VA ECMO initiation. Interleukin 6 and 8 serum levels in nonsurviving patients were significantly elevated on day 1 of VA ECMO. Receiver operating characteristics analysis revealed significant prognostic impact of interleukin 6 and 8 on day 1 of VA ECMO (AUC 0.70 and 0.72). Survival analysis comparing patients above and below the cutoff showed a 1‐year survival of 32.6% for IL6 and 20.8% for IL8 above, as well as 66.9% for IL6 and 61.9% for IL8 below the cutoff ( P < .05). Interleukin 6 and 8 serum levels demonstrated prognostic value early in VA ECMO therapy. The technical applicability of interleukin reduction raises interest in interleukins 6 and 8 as therapeutic targets.